Dicatet Mak! - Endang Purwasari (Emik, 2020)
Debt has been a common phenomenon in people’s lives, both in the big cities, as well as in remote areas. This debt activity has been internalized into people's lives so that it cannot be separated no matter how small. There are quite a number of existing related literatures that deal with this. However, debt is only seen as a means to meet the daily needs of debtors, in which the relationship between creditors and debtors is not far enough studied. The study related to the relationship between creditors and debtors (if any) is still limited. This article seeks to complement the existing literature by examining debt and credit cyrcle that create new relationships in the spectrum of oil palm plantation employees. This ethnographic study takes place in the housing complex of oil palm plantation employees in Kebun Sei Muara, Kalimantan Island. It involved 26 female informants consisting of six women workers, six housewives, and fourteen female traders. Data was collected using in-depth interview in order to explor the reasons for debt, reason for giving debt, the implication of debt, and how parties are related to debt. While participatory observation is carried out by participating in the daily activities of the Kebun Sei Muara community, such as shopping at a food stall, attending parties, helping in various parties, gossiping, social gathering, etc. The study indicates that debt has become the foundation of reciprocity relations in Kebun Sei Muara. This debt is carried out for from daily needs to the need for making life cycle parties, which involve not only the poor, but also rich people. This creates a reciprocal bond between the debtor and the creditor, the host and the guests, as well as creates balanced reciprocity between them. This relationship raises an obligation for both actors involved to give and return the contribution for the attending parties. In this context, there is a norm that requires them to come to provide contribution in the form of money and/or goods to the host, and expecting to have a balanced reciprocity in return. The higher the status, the bigger the party, the more debts the host make, and the return contribution will be used to pay for the debt. The higher the status, the more contribution the guests have to provide, though it depends on the closeness between the host and the guests, as well their previous contribution. Community members, who do not participate in the debt circle, will automatically be ostracized from social activities and are considered as “the others”. Conflict potentially occurs between debtor and creditor when payment is neglected, but this is depended on how the creditor responds to it. It is common, however, that this may be impacted on the future relationship not only between the two, but also with others in the Kebun Sei Muara.